DISSECTING THE GLOCALISATION OF CHINESE REALITY TV SHOWS - Ong'ong'a, Oloo Daniel (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
The Chinese media has expanded significantly in recent years along with the country's interest in investing in emerging nations as its relations with these nations deepen and with the spread of Chinese culture through the media. Since the Chinese government began implementing substantial projects in countries in Africa, the Caribbean, and Asia, the Chinese media has been distinguished by localizing its television programming to compete with the host countries and extending their feeling of soft power to these nations. The Chinese reality television programs have remained to be a staple of the television programming in their host nations despite encountering substantial hurdles related to cultural differences and technical advancement. Despite significant pushback from the initial global dominant media in these markets, Chinese reality television series have persisted to be part of the regular host countries' television program diet. As a result, this study examines these patterns with a focus on Chinese reality television shows that have entered the host countries' markets, as well as the motive for their evolution. The paper examines the extent to which states might use these tactics to balance their domestic production while maintaining friendly relations with China. It is critical to smidgeon the evolution of this critical phenomenon in the philosophical context of product internationalization and marketization. The article addresses these difficulties by drawing attention to them from many actors in this prominent field. This study is crucial because it debunks widespread myths about reality television, such as the notion that viewers should not expect spontaneous, unscripted programming. The morality of the claimed programming of reality television programs may even be considered. To cite this article (7th APA style): Ong’ong’a, O. D. (2021). Dissecting the glocalization of Chinese reality TV shows. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(2), 142-150. http://dx.doi.org/10.36782/jcs.v11i2.2035